New structure of dual stator hybrid excitation flux switching motor for aircraft applications - Soomro, Hassan Ali (2021)
Aircraft applications demand high reliability, high torque and power densities while aiming to reduce weight, complexity, fuel consumption, costs, and environmental impact. New electric driven system such as flux switching machine (FSM) has been developed which is capable to meet these requirements as well as providing significant technical and economic improvements over conventional systems. However, FSMs with single stator associated with limited free space for active sources in stator, which leads to some drawbacks of complicated structure, less paths for flux flow, flux cancellations, and heat generation effects. To overcome these issues, FSMs using double stator (DS) have been proposed by many researchers which provide more free space for active sources and flux to flow. Whereas, these structures show some drawbacks of flux cancelations are saturations due to the arrangement of excitation sources in both stators. Therefore, this research presents design studies of new DS hybrid excitation FSM (DS HEFSMs) having permanent magnets (PMs) in inner stator while field excitation coil (FEC) and armature coils in outer stator so that coils can be easily inserted or replaced during fault conditions. Moreover, the performance analysis of proposed design is investigated and compared with existing DS designs based on 2D finite element analysis (FEA) using JMAG software ver. 16.0 In addition to obtain the optimum torque and power, proposed DS HEFSM is optimized by treating several design parameters defined in the rotor segments, armature slot, and FEC slot using deterministic optimization approach. Accordingly, the optimized design shows the capabilities to achieved 19.6% better flux linkage compared to initial design along with 38.67%, 30.58% and 2.91% increment in torque density, power density and in efficiency respectively. While, the torque and power achieved by final design are 17% and 58% more than existing PM synchronous motor (PMSM) respectively used for aircraft propeller applications. Finally, in this research it is concluded that the proposed DS HEFSM has shown the promising capabilities to achieve higher torque densities at maximum speed ranges and can be installed in various single seated aircrafts to fly at various altitudes.